An MRI approach to assess placental function in healthy humans and sheep. (29th March 2021) - Saini, Brahmdeep S.; Darby, Jack R. T.; Marini, Davide; Portnoy, Sharon; Lock, Mitchell C.; Yin Soo, Jia; Holman, Stacey L.; Perumal, Sunthara R.; Wald, Rachel M.; Windrim, Rory; Macgowan, Christopher K.; Kingdom, John C.; et al.
Abstract : Key points: Human placental function is evaluated using non‐invasive Doppler ultrasound of umbilical and uterine artery pulsatility indices as measures of resistance in placental vascular beds, while measurement of placental oxygen consumption ( V O 2 ) is only possible during Caesarean delivery. This study shows the feasibility of using magnetic resonance imaging (MRI) in utero to measure blood flow and oxygen content in uterine and umbilical vessels to calculate oxygen delivery to and V O 2 by the gravid uterus, uteroplacenta and fetus. Normal late gestational human uteroplacental V O 2 by MRI was ∼4 ml min −1 kg −1 fetal weight, which was similar to our MRI measurements in sheep and to those previously measured using invasive techniques. Our MRI approach can quantify uteroplacental V O 2, which involves the quantification of maternal‐ and fetal‐placental blood flows, fetal oxygen delivery and V O 2, and the oxygen gradient between uterine‐ and umbilical‐venous blood, providing a comprehensive assessment of placental function with clinical potential. Abstract: It has not been feasible to perform routine clinical measurement of human placental oxygen consumption ( V O 2 ) and in vitro studies do not reflect true metabolism in utero . Here we propose an MRI method to non‐invasively quantify in utero placental and fetal oxygen delivery ( D O 2 ) and V O 2 in healthy humans and sheep. Women ( n = 20) and Merino sheep ( n = 10; 23 sets of measurements) with singleton pregnancies underwent an MRI in late gestation (36 ± 2 weeks and 128 ± 9 days, respectively; mean ± SD). Blood flow (phase‐contrast) and oxygen content (T1 and T2 relaxometry) were measured in the major uterine‐ and umbilical‐placental vessels, allowing calculation of uteroplacental and fetal D O 2 and V O 2 . Maternal D O 2 (ml min −1 kg −1 fetus) to the gravid uterus was similar in humans and sheep (human = 54 ± 15, sheep = 53 ± 21, P = 0.854), while fetal D O 2 (human = 25 ± 4, sheep = 22 ± 5, P = 0.049) was slightly lower in sheep. Uteroplacental and fetal V O 2 (ml min −1 kg −1 fetus; uteroplacental: human = 4.1 ± 1.5, sheep = 3.5 ± 1.9, P = 0.281; fetus: human = 6.8 ± 1.3, sheep = 7.2 ± 1.7, P = 0.426) were similar between species. Late gestational uteroplacental:fetal V O 2 ratio did not change with age (human, P = 0.256; sheep, P = 0.121). Human umbilical blood flow (ml min −1 kg −1 fetus) decreased with advancing age ( P = 0.008), while fetal V O 2 was preserved through an increase in oxygen extraction ( P = 0.046). By contrast, sheep fetal V O 2 was preserved through stable umbilical flow (ml min −1 kg −1 ; P = 0.443) and oxygen extraction ( P = 0.582). MRI derived measurements of uteroplacental and fetal V O 2 between humans and sheep were similar and in keeping with prior data obtained using invasive techniques. Taken together, these data confirm the reliability of our approach, which offers a novel clinical 'placental function test'. Key points: Human placental function is evaluated using non‐invasive Doppler ultrasound of umbilical and uterine artery pulsatility indices as measures of resistance in placental vascular beds, while measurement of placental oxygen consumption ( V O 2 ) is only possible during Caesarean delivery. This study shows the feasibility of using magnetic resonance imaging (MRI) in utero to measure blood flow and oxygen content in uterine and umbilical vessels to calculate oxygen delivery to and V O 2 by the gravid uterus, uteroplacenta and fetus. Normal late gestational human uteroplacental V O 2 by MRI was ∼4 ml min −1 kg −1 fetal weight, which was similar to our MRI measurements in sheep and to those previously measured using invasive techniques. Our MRI approach can quantify uteroplacental V O 2, which involves the quantification of maternal‐ and fetal‐placental blood flows, fetal oxygen delivery and V O 2, and the oxygen gradient between uterine‐ and umbilical‐venous blood, providing a comprehensive assessment of placental function with clinical potential.